Population aging, older workers, and Canada's labour force - Frank T. Denton; Byron G. Spencer (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2009)
The Expert Panel on Older Workers made recommendations designed to increase the labour force participation of older workers. We explore the implications that higher rates of older-worker participation would have for the overall size and age composition of the labour force, for the productive capacity of the economy, and for the incomes of Canadians. Our purpose is to assess the potential impact that increased participation of older workers might have in offsetting any anticipated adverse effects of population aging on standards of living.
Keywords: J21; J24; J26; 330; older worker; participation rates; productive capacity; population aging; Bevölkerungsentwicklung; Alternde Bevölkerung; Arbeitsmarkt; Erwerbspersonenpotenzial; Prognose; Kanada